EFL STUDENTS’ PERCEPTION OF ETHICAL CONCERNS ON USING CHATGPT IN ACADEMIC WRITING - Pasaribu, Arsen Nahum; Manik, Sondang; Pasaribu, Tiara Kristina; Sibagariang, Ruth Olga; Saragih, Yohana Insani (English Review: Journal of English Education, 2025)
In recent years, there has been an increased interest in the application of artificial intelligence (AI), namely ChatGPT, for educational purposes. However, EFL students' insights of the ethical use of using ChatGPT in academic writing remain unexplored. The purpose of this study is to reveal the EFL students' perspectives on the ethical use of Chat GPT in academic writing. Data were obtained from 54 EFL students who have taken academic writing course by using a Likert Scale questionnaire, with a focus on ethical issues such as plagiarism, academic integrity, over-reliance on ChatGPT, data biases, and unclear guidelines. The findings show that students significantly concerns about the ethical use of ChatGPT, though a small number remain unaware of these issues. The study recommends incorporating ethical education regarding ChatGPT into academic curricula. Lecturers or teachers should focus on helping students understand the ethical challenges related to the application of ChatGPT, such as plagiarism and bias. Additionally, clear guidelines for ChatGPT use in academic writing should be established to promote academic integrity and responsible ChatGPT use.